Fludarabine therapy in Waldenström's macroglobulinemia - Dimopoulos, M.A.; O'Brien, S.; Kantarjian, H.; Pierce, S.; Delasalle, K.; Barlogie, B.; Alexanian, R.; Keating, M.J. (The American Journal of Medicine, 1993)
purpose: To assess the response rate, remission duration, and survival of patients with Waldenström's macroglobulinemia treated with the adenine nucleoside analogue fludarabine. patients and methods: Twenty-eight patients with Waldenström's macroglobulinernia, of whom only 2 were previously untreated, received fludarabine at a dose of 20 to 30 mg/m2 intravenously daily for 5 days (20 patients) or 30 mg/m2 intravenously daily for 3 days (8 patients). Treatment was continued until maximum response was achieved. Responding patients were followed with no further treatment until relapse. results: Ten patients responded (36%), including the 2 previously untreated patients and 8 of 26 patients (31%) who were resistant to prior therapies. Uninaintained remissions lasted for a median of 38 months. There were no fatalities associated with this treatment. Previously untreated patients and those with a primary resistant disease of relatively short duration were more likely to benefit from this treatment. conclusion: Fludarabine is an effective salvage agent for the treatment of patients with resistant Waldenström's macroglobulinemia. Further investigations of fludarabine in untreated patients and in combination with other active agents are warranted. © 1993.